Potential of Microalgae for Biofuel and Food Production - Tan, Yeong Hwang; Chai, Mee Kin; Wong, Ling Shing (INTI International University, 2022)
With the continuous increase of global population, energy and hunger are the critical crisis that humankind facing in this century. Microalgae has been proposed as the solution due to the presence of the various metabolite and their attractive features. This review summaries the potential of microalgae as the feedstock for biofuel and food production. The literature indicated that the abundance of suitable fatty acid in microalgae can be used for biodiesel production while other bio-components such as carbohydrate can be used for biogas and bioethanol production. Apart from biofuel production, presence of high-quality protein, fatty acid, polysaccharides, vitamin, minerals and other bio-components with benefit biological properties in microalgae spur it as dedicated candidates for food production. However, the microalgae derived biofuel and food are still not available at the moment. The challenges that might need to be confront prior to industrial production are also briefly discussed in this review.